Evaluation of Skin Irritation and Acute and Subacute Oral Toxicity of Lavandula angustifolia Essential Oils in Rabbit and Mice. (27th January 2019) - Mekonnen, Awol; Tesfaye, Solomon; Christos, Selam G.; Dires, Kassahun; Zenebe, Tizazu; Zegeye, Nigus; Shiferaw, Yoseph; Lulekal, Ermias
Abstract : Lavandula angustifolia is used in traditional and folk medicines of Ankober District, North Central Ethiopia, for the treatment of several livestock and human disorders. This toxicity study aimed to investigate L. angustifolia essential oil oral toxicity in mice and skin irritation in rabbit. L. angustifolia essential oil was analyzed using gas chromatography-mass spectrometry methods and showed predominance of Eucalyptol (52.36%), Camphor (11.91%), gamma-terpinene (8.775%) and endoborneol (7.585%). Limit test at 2000 mg/kg dose was used for L. angustifolia essential oil acute toxicity test and revealed LD50 value was higher than 2000 mg/kg. For subacute toxicity study 2000mg/kg was given orally to each mouse for 21 days. The result demonstrated no significant changes (p > 0.05) in the body weights, and biochemical parameters, gross abnormalities, water, and food intake were observed. No macroscopic changes were seen in the histopathology analysis of kidneys and livers. For skin irritation test shaved rabbit skin was treated with 10% ointment formulation. Ointment of L. angustifolia oil did not affect mice skin. Generally, this toxicity study demonstrated that L. angustifolia essential oil is nontoxic.